Conservative culture à la mode: contemporary Chinese Buddhism facing globalization - Li, Silong (Studies in Chinese Religions, 2017)
Following Chinese economic reform, Chinese Buddhism, having regained its energy, shook off the title of ‘superstition’ or ‘opium’ and became a new fashion for Chinese society overnight. Contemporary Chinese Buddhism (mainly referring to the Han Chinese Buddhism in Mainland China in this article), by means of modern communication technologies such as websites, Weibo and Wechat, keeps expanding its influence, gaining rich social resources and, on advocating ‘Humanistic Buddhism,’ engaging itself actively in various areas such as education, charity and health care, which allows it to take an active part in the development of the Chinese economy. However, in the meantime, the revival of Contemporary Chinese Buddhism also maintains and restores the traditional Buddhist regime and monastic life. Facing the tendency towards the commercialization and secularization of monastic communities, Chinese Buddhism always brings up the principle of ‘taking precepts as mentor.’ Even among the younger generation of monks, who aspire to the re-establishment of the monastic regime of the Ming and Qing, we still find a clear presence of cultural conservatism. These all pushed Contemporary Chinese Buddhism into a slightly unfavorable position compared to Christianity.